Observational study on cases of sepsis in the State of Pará from 2015 to 2019 (Research, Society and Development, 2022)
Sepsis can be understood as a set of infections throughout the body. Worldwide, its incidence is estimated at around 15 to 19 million cases annually. Recently, deaths have decreased, reaching an estimated value of 20 to 40% of reported cases. However, in Brazil, according to data from the Instituto Latino Americano de Sepsis (Ilas), death from sepsis corresponds to 65% of all deaths, which is much higher than the world estimate. Thus, in this paper, we will evaluate mortality from sepsis in the State of Pará from 2015 to 2019. An ecological observational study was carried out using the data collected in the Mortality Information System and the Hospital Information System, made available by the Department of Informatics of the Unified Health System in Brazil. During the period investigated, a total of 2,547 deaths from sepsis were recorded. The epidemiological profile of mortality from sepsis presented individuals with the following characteristics: male, mixed race, 1 to 3 years of schooling, marital status: a married, place of occurrence: hospital, and age group from 60 to 79 years. It is of fundamental importance to develop more targeted prevention policies, prioritize educational and population awareness measures, and the continuous improvement of health teams regarding the knowledge of sepsis about early identification and more effective care to reduce mortality from sepsis in the state of Pará, Brazil.